The Influence Of Digital Marketing, Brand Ambassador And Electronic Word Of Mouth On Purchasing Decisions For Nivea Body Lotion Product In Pekanbaru - Nazwa Aqiila Putri; Henni Noviasari; Sri Wahyuni Wildah (West Science Business and Management, 2024)
This research was conducted with the aim of knowing the effect of Digital Marketing, Brand Ambassadors and Electronic Word Of Mouth on Purchasing Decisions for Nivea Body Lotion products in Pekanbaru. The population in this study were Pekanbaru people who had bought Nivea Body Lotion. The method used in this research is descriptive and quantitative, with research data sources coming from primary and secondary data. The number of samples in this study amounted to 105 people with the sampling technique using purposive sampling technique. The method of analysis of this research is multiple linear regression analysis and through validity tests and reliability tests. In this study, the results obtained that Digital Marketing has a significant influence on purchasing decisions for Nivea body lotion products in Pekanbaru, Brand Ambassadors have a significant effect on purchasing decisions for Nivea body lotion products in Pekanbaru, and Electronic Word of Mouth on purchasing decisions for Nivea body lotion products in Pekanbaru.